ANALYSIS AND CHARACTERIZATION OF POLYDIMETHYLSILOXANE (PDMS) SUBSTRATE BY USING UNIAXIAL TENSILE TEST AND MOONEY-RIVLIN HYPERELASTIC MODEL - Zulfiqar, S.; Saad, A.A.; Ahmad, Z.; Yusof, F.; Fakpan, K. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
Polydimethylsiloxane (PDMS) is the most widely used silicone polymer in the development of microfluidic devices, sensors, medical appliances and stretchable electronic devices. PDMS Sylgard 184 from Dow Corning is obtained by mixing only base polymer and cross-linking agent in a certain ratio which is more expensive than other types of PDMS and difficult to cure when reacting with rubber like materials and plastics. Also, the tensile testing of such type of substrate is impossible to carry out at higher cross linking ratio (30:1) and above. To overcome these issues, this study proposed a new formulation to fabricate PDMS substrate by mixing base polymer PDMS-OH (PDMS hydroxy terminated) with different chemicals that act as cross-linking agent, organic solvent, viscosity controller and catalyst. The mixing is done at 200-250 rpm using magnetic or mechanical stirrer. The prepared formulation is then poured into three dog bone shaped molds (based on ASTM D412 Type C standard) and allowed to cure at room temperature for 24 hrs. The tensile strength is then characterized by uniaxial tensile test on UTM machine. Mooney-Rivlin (5 and 9 parameters) model is implemented on engineering stress strain data in ANSYS to validate the obtained strain rate and material constants associated with this hyperelastic model are obtained by curve fitting damped least squared method. Also, the maximum stress obtained by UTM testing is 2.18 MPa before failure at 300% strain rate. The MR models are validated by calculating coefficient of determination R2 values. The R2 values of MR5 and MR9 parameters models are 0.9914 and 0.9994, respectively.